A novel magnetic nanoscaled Fe3O4/CeO2 composite prepared by oxidation-precipitation process and its application for degradation of orange G in aqueous solution as Fenton-like heterogeneous catalyst. (February 2017) - Gan, Guoqiang; Liu, Juan; Zhu, Zhixi; Yang, Ziran; Zhang, Conglu; Hou, Xiaohong
Abstract: In this work, magnetic nanoparticles (MNPs) Fe3 O4 /CeO2 were firstly synthesized using three different preparation methods, including coprecipitation, impregnation oxidation-precipitation and impregnation reduction-precipitation, respectively. The catalytic activities of Fe3 O4 /CeO2 MNPs, prepared by above three methods, were compared systematically in terms of the degradation of orange G (OG). The impregnation oxidation-precipitation process was economical and maneuverable due to the usage of air, no need of nitrogen protection and higher utilization efficiency of iron. Response surface methodology based on central composite design were used to investigate the individual and interactive effects of three process parameters on the OG degradation, i.e. the initial pH of the solution, the dosage of H2 O2 and the initial concentration of OG. Under the optimal conditions of pH 2.5, H2 O2 30 mM, OG 50 mg L −1, catalyst 2.0 g L −1 and 35 °C, the degradation percentage of OG was 98.2% within 120 min, which agreed well with the modeling prediction (R 2 = 0.9984, and Adj-R 2 = 0.9969). And the degradation reaction well followed the first-order kinetic with R 2 = 0.9969. The Fe3 O4 /CeO2 -OX MNPs showed high catalytic activity, stability and reusability in the degradation of OG. Graphical abstract: Highlights: Fe3 O4 /CeO2 MNPs were prepared via oxidation-, reduction- and co-precipitation methods. Fe3 O4 /CeO2 was firstly used for the degradation of azo dye as Fenton-like heterogeneous catalyst. Fe3 O4 /CeO2 -OX exhibited excellent sustained catalytic ability and reusability.